Postural stability in goalkeepers of the Polish national junior handball team - Wilczynski, J. (Journal of Human Kinetics, 2018)
The aim of the study was to assess postural stability of goalkeepers from the Polish national junior handball team. Eleven juniors of the Polish national handball team (age 16.82 ± 1.6 years, body height 191.27 ± 3.1 cm, body mass 88.41 ± 12.26 kg, BMI 24.18 ± 3.22 kg/m2) were selected for the study. The Biodex Balance System and AccuGait AM¬TI platform were used to evaluate postural stability. The obtained results indicated good postural stability of the subjects. During the Biodex Balance System platform tests, all subjects presented very good postural stability and maintained within Zone A. Postural sway was greater in the sagittal plane compared to the frontal one. Most of the participants demonstrated slight backward tilts, but maintained in Quadrant IV. During the AccuGait AMTI platform trial, Path Length and Average COP Speed significantly increased in the test performed with closed eyes. Furthermore, there were significant positive correlations between the number of variables obtained during the Biodex Balance System and AccuGait AMTI tests. Proper and stable posture are necessary conditions to be met to carry out most free movements and locomotion. They play a significant role in the game of a handball goalkeeper and for that reason, postural stability testing of handball goalkeepers is an important element of coordination training. Thus, the use of postural stability exercises implementing the biofeedback method on stabilo and dynamometric platforms is practical and justifiable.